Frontal-Lobe Dysfunction in Schizophrenia and Obsessive-Compulsive Disorder - A Neuropsychological Study - Abbruzzese, M.; Bellodi, L.; Ferri, S.; Scarone, S. (Brain and cognition, 1995)
Converging evidence suggests there is a specific role of dorso-lateral-prefrontal cortex (DLPC) in schizophrenic disorders and of orbite-frontal cortex (OFC) in obsessive-compulsive disorder (OCD). Here, 25 schizophrenic and 25 OCD patients were evaluated with Wisconsin Card Sorting Test and Object Alternation Test; neuropsychological tools sensitive to DLPC and OFC damage, respectively; and compared with 25 subjects of a control group. Moreover, they all underwent Weigls Sorting Test and the Word Fluency Test to assess global frontal functioning. The results indicated a DLPC deficit in schizophrenia and an OFC involvement in OCD. These data suggest that functional disorders of the central nervous system can be explored with neuropsychological instruments.